LEKSIKON BAHASA JAWA DALAM BAHASA SUNDA DI KABUPATEN BREBES - Siti Junawaroh Ashari Hidayat (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
There are two languages spoken in the community in the district of Brebes, the Javanese and Sundanese. Sundanese language of Brebes is growing in the Java language. Sundanese-speaking community in the region to interact and communicate well with the Java language speakers. Therefore, the language used by the Sundanese people in the region are expected to be affected the Java language used by the majority of Brebes. The effect is most apparent at the level of the lexicon. Java language lexicon is absorbed in Sundanese in Brebes occurred in full and with the change. Based on the research conducted, which absorbed the full lexicon present in several categories, namely nouns, verbs, adjectives, adverbs, and numeral. Java language lexicon is absorbed in Sundanese Brebes with changes in the process of sound attenuation, sound reinforcement, the removal of noise, the addition of sound, assimilation, and dissimilation.